Genesis and Historical Sense of the Motto “Liberté, Égalité, Fraternité” - Dorskaia, Aleksandra; Dorskii, Andrei (Տիգրան Մեծ)
The study is devoted to the formation of the motto of the French Revolution Ŕ Liberté, Égalité, Fraternité. The hypotheses as to its emergence are considered, notably the invention of the triad by J.Locke, F.Fénelon, French enlighteners and Masons. Based on the analysis of the texts pertaining to the alleged authors of the motto, it is concluded that its spread was taking place only during the Revolution. The meaning of liberty, equality and fraternity is seen as an expression of the fundamental values of the Modern Age; the interdependence of these concepts is demonstrated.
Keywords: Liberté; Philosophy of Law